2020
DOI: 10.1007/s13202-020-00862-z
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive investigation of low-salinity waterflooding in sandstone reservoirs

Abstract: Waterflooding has been applied for many years as secondary recovery method with no or little regard to the effect of the injected water salinity on oil recovery. However, in the last decade, there has been an increasing interest in understanding the effects of changing injected water salinity on reservoir performance. The potential of low-salinity waterflooding (LSWF) has been studied in sandstone reservoirs by numerous core-flooding experiments. These experiments have shown diverse results. This paper aims to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 82 publications
1
1
0
1
Order By: Relevance
“…In addition, Alotaibi and Nasr-El-Din (2019) suggested that there is a critical salinity (not the lowest), at which the IFT between oil and brine is at a minimum level. Snosy et al (2020) and Snosy et al (2021) reported the same results from the sandstone reservoir.…”
Section: Salinity Range For the Lswf Applicationssupporting
confidence: 63%
“…In addition, Alotaibi and Nasr-El-Din (2019) suggested that there is a critical salinity (not the lowest), at which the IFT between oil and brine is at a minimum level. Snosy et al (2020) and Snosy et al (2021) reported the same results from the sandstone reservoir.…”
Section: Salinity Range For the Lswf Applicationssupporting
confidence: 63%
“…Factorial design is an important statistical method for optimizing and simplifying laboratory experiments by investigating the effects of multiple controllable factors on interest responses 34 , 57 . These statistical evaluations of gas viscosity were conducted using Minitab software 55 .…”
Section: Resultsmentioning
confidence: 99%
“…Each group uses different techniques based on the injection of fluids or other agents to modify certain physical and/or chemical properties, either in the fluids or in the reservoir, improving the oil recovery [6]. According to the EOR aforementioned classification, Low Salinity Waterflooding (LSW) is usually envisioned as a chemical EOR method consisting of injecting low salinity brine that is depleted of divalent cations compared to in-situ brine into the reservoirs, as demonstrated in numerous core-flooding experiments in sandstone rocks [7]. However, due to the complexity of crude oil-brine-rock interactions, the underlying mechanism of LSW has been debated in the literature for the past two decades [8].…”
Section: Introduction 41mentioning
confidence: 99%